Self-efficacy change associated with a cognitive load-based intervention in an undergraduate biology course. (August 2018) - Feldon, David F.; Franco, Joana; Chao, Jie; Peugh, James; Maahs-Fladung, Cathy
Abstract: Cognitive load theory (CLT) holds that discovery learning and other instructional strategies imposing high levels of extraneous load on novice learners hinder learning. Such learning conditions are also associated with significant drops in persistence, a key measure of motivation. However, research within the CLT framework typically engages motivation as a necessary precursor to learning, rather than as an outcome of instruction. In this study, we examine changes in motivational beliefs as outcomes of learners' cognitive processes through a CLT lens as they engage with instruction. Using a double-blind quasi-experimental design, we manipulate the level of cognitive load imposed on participants through instruction and assess changes in self-efficacy from pre-to post-intervention. In an analysis of data from students enrolled in an undergraduate biology course (n = 2078), students in the treatment condition demonstrated significantly higher performance on end-of-semester lab reports and self-efficacy measures. However, post-instruction self-efficacy was not significantly related to performance, controlling for pre-instruction self-efficacy, gender, and scientific reasoning ability. These findings introduce the possibility that the cognitive load imposed on working memory during instruction may affect motivational beliefs and provides a foundation to further explore connections between historically distinct theoretical frameworks such as CLT and social cognitive theory. Highlights: Cognitive task analysis-based instruction yields better student performance. Cognitive task analysis-based instruction imposes less extraneous cognitive load. Extraneous cognitive load decreases self-efficacy independent of performance.